If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n-6=-10
We simplify the equation to the form, which is simple to understand
n-6=-10
We move all terms containing n to the left and all other terms to the right.
+1n=-10+6
We simplify left and right side of the equation.
+1n=-4
We divide both sides of the equation by 1 to get n.
n=-4
| 0=x^2-25x+144 | | 9(5+x)=15(10+x) | | 4x-(9-3x)=18x-1 | | w=4+8 | | 15-j+5j+2=-14 | | p=4+8 | | -4(x+4)=5-(-4) | | 2(-18)+3=3(-18)+7 | | -5(x+7)=5-(-1) | | 4x=3(49-x) | | 5+h=-6 | | .67x=5 | | 17.50+4p=53.50 | | 7-5m=45 | | 2(5x+2)=8x | | -4(3x+1)+x=3x+10 | | .5*.5*.5*.5= | | 10-4x=28 | | 98x=-1 | | x^2-19x+9=0 | | 14x-2=7x-51 | | 3(6x)=200 | | 5(m-3)+2m=28 | | (x-1)7=8x | | C+9=-13 | | 9r+5=71 | | 10+10+(-7)+(-5)= | | 15r+6=54 | | -47+47=-24p-14p | | 3x=2x+16 | | -47+58=-24p-14p | | 6x-15=3x+1 |